Impact of discordance between patient's and evaluator's global assessment on treatment outcomes in 14 868 patients with spondyloarthritis - Michelsen, Brigitte; Ornbjerg, Lykke Midtboll; Kvien, Tore K.; Pavelka, Karel; Nissen, Michael J.; Nordstrom, Dan; Ostergaard, Mikkel (Oxford Univ Press, 2020)
Objectives. To assess the impact of 'patient's minus evaluator's global assessment of disease activity' (Delta PEG) at treatment initiation on retention and remission rates of TNF inhibitors (TNFi) in psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) patients across Europe. Methods. Real-life data from PsA and axSpA patients starting their first TNFi from 11 countries in the European Spondyloarthritis Research Collaboration Network were pooled. Retention rates were compared by Kaplan-Meier analyses with log-rank test and by Cox regression, and remission rates by chi(2) test and by logistic regression across quartiles of baseline Delta PEG, separately in female and male PsA and axSpA patients. Results. We included 14 868 spondyloarthritis (5855 PsA, 9013 axSpA) patients. Baseline Delta PEG was negatively associated with 6/12/24-months' TNFi retention rates in female and male PsA and axSpA patients (P < 0.001), with 6/12/24-months' BASDAI < 2 (P <= 0.002) and ASDAS < 1.3 (P <= 0.005) in axSpA patients, and with DAS28CRP(4)<2.6 (P <= 0.04) and DAPSA28 <= 4 (P <= 0.01), but not DAS28CRP(3)<2.6 (P >= 0.13) in PsA patients, with few exceptions on remission rates. Retention and remission rates were overall lower in female than male patients. Conclusion. High baseline patient's compared with evaluator's global assessment was associated with lower 6/12/24-months' remission as well as retention rates of first TNFi in both PsA and axSpA patients. These results highlight the importance of discordance between patient's and evaluator's perspective on disease outcomes.
Keywords: axial spondyloarthritis; psoriatic arthritis; TNF inhibitors; treatment outcomes